Body mass index evaluation in hypertensive women - Raimunda Magalhães da Silva; Zélia Maria de Sousa Araújo Santos; Samélia Léa Menezes Becker (Revista Brasileira em Promoção da Saúde, 2003)
Hypertension prevalence is approximately three times higher in obese people. This study analyzed the Body Mass Index (BMI) in 200 hypertensive women in follow up treatment in a public hypertension center in the city of Fortaleza-CE, Brazil. Sixty-one percent or 122 have incomplete primary school levels; 118 (59%) had family incomes from 1 to 2 minimum wages, (US$90.00-US$190.00). Sixty one percent were obese and 30% were overweight; 150 (75%) had hypertension cases in the family, as well as 98 (49%) had cases of acute myocardium infarct and 97 (48%) of vascular cerebral stroke in the family. Our results indicate variation of Body Mass Index especially in obese and then in overweight women. An efficient follow up treatment is fundamental specifically for those patients due to cardiovascular and cardio cerebral risks.